Comprehensive Assessment of Transient Stability for Grid-Forming Converters Considering Current Limitations, Inertia and Damping Effects - Jinlei Chen; Qingyuan Gong; Yawen Zhang; Muhammad Fawad; Sheng Wang; Chuanyue Li; Jun Liang (CSEE Journal of Power and Energy Systems)
This paper presents a quantitative assessment of the transient stability of grid-forming converters, considering current limitations, inertia, and damping effects. The contributions are summarized in two main aspects: First, the analysis delves into transient stability under a general voltage sag scenario for a converter subject to current limitations. When the voltage sag exceeds a critical threshold, transient instability arises, with its severity influenced by the inertia and damping coefficients within the swing equation. Second, a comprehensive evaluation of these inertia and damping effects is conducted using a model-based phase-portrait approach. This method allows for an accurate assessment of critical clearing time (CCT) and critical clearing angle (CCA) across varying inertia and damping coefficients. Leveraging data obtained from the phase portrait, an artificial neural network (ANN) method is presented to model CCT and CCA accurately. This precise estimation of CCT enables the extension of practical operation time under faults compared to conservative assessments based on equal-area criteria (EAC), thereby fully exploiting the system's low-voltage-ride-through (LVRT) and fault-ride-through (FRT) capabilities. The theoretical transient analysis and estimation method proposed in this paper are validated through PSCAD/EMTDC simulations.